Theories for the New Millennium: The Deployment of Theory in LIS Research - McKechnie, Lynne E.F.; Pettigrew, Karen E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
We report on our findings to date regarding authors' use of theory in articles that appeared in JASIS and LISR from 1993-97. Our preliminary findings indicate that theory was discussed in 36% of the articles, and that the majority of these theories were from the social sciences (44.9%), followed by LIS (29.8%), the sciences (18.2%), and humanities (7.1%).